Domesticating the church: the reuse of urban churches as loft living in the post-secular city. (2nd October 2016) - Lynch, Nicholas
Abstract: In recent years, numerous mainline Christian denominations throughout Canada have sold their places of worship in the real estate market in response to declines in religious membership and participation. At the same time, a growing demand for creative residential spaces by a group of the new middle class encourages the redevelopment of churches into upscale lofts, a practice connected to but divergent from the post-industrial loft living made popular in cities like New York. In this paper, I explore how the production and consumption of churches as lofts represents a novel terrain of private urban redevelopment. Church lofts are an emergent form of housing and the latest frontier in the remaking of material, cultural and religious landscapes in the post-secular city – a context where novel forms of secularity take shape alongside new expressions of religion. With an empirical focus on Toronto, I investigate how 'redundant' worship spaces are appropriated and transformed into private domestic spaces of commodified religion and heritage. Rebuilt as unique but exclusive places to live, church lofts are part of a secular upscaling of the central city, a process that increasingly remakes the city as a place of capital reinvestment, middle-class colonization and socio-secular upgrading.